Polysaccharide-Zein Composite Nanoparticles for Enhancing Cellular Uptake and Oral Bioavailability of Curcumin: Characterization, Anti-colorectal Cancer Effect, and Pharmacokinetics - Liu, Lu; Yang, Shufang; Chen, Feng; Cheng, Ka-Wing (Frontiers in Nutrition, 2022)
Curcumin (CUR) has demonstrated promising potential as a therapeutic agent against colorectal cancer (CRC). However, its intrinsic shortcomings, including oxidative instability, sensitivity to gastrointestinal (GI) hydrolytic/enzymatic action, and susceptibility to biotransformation and systemic elimination, have greatly undermined its value for application in clinical settings. The development of carriers, in particular oral formulations, for its efficient delivery has remained an important direction in nutraceutical research. In the present work, CUR-encapsulated nanoparticles were fabricated with zein alone (Zein-CUR) and with zein and a polysaccharide (PS) [gum Arabic (GA), hyaluronic acid (HA) and pectin (PC), respectively] (PS-Zein-CUR). Their physicochemical and biological properties were evaluated in a series of in vitro and in vivo assays. Dynamic light scattering analysis showed an increase in the particle size of the nanoparticles from 129.0 nm (Zein-CUR) to 188.8–346.4 nm (PS-Zein-CUR). The three PS-Zein-CUR formulations had significantly higher (17–22%) CUR encapsulation efficiency (EE) than Zein-CUR. Among them, HA-Zein-CUR exhibited the highest EE and loading capacity. Zeta potential and FTIR spectra indicated the involvement of electrostatic and hydrophobic interactions and hydrogen bonds in the formation of the PS-Zein-CUR. In human CRC cell lines (HCT8, HCT29, and HCT116), the three PS-Zein-CUR and CUR all effectively inhibited cell viability and colony formation (HA-Zein-CUR > PC-Zein-CUR > GA-Zein-CUR/CUR). HA-Zein-CUR and PC-Zein-CUR also resulted in significantly higher cellular uptake of CUR than GA-Zein-CUR and CUR. Simulated GI-digestion assay demonstrated significantly improved controlled-release properties of these two formulations. Further pharmacokinetics and tissue distribution assays in a CRC subcutaneous xenograft model in nude mice corroborated the enhanced pharmacokinetic properties of intragastric administration of HA-Zein-CUR compared with that of free CUR (3 times higher Cmax and 9.18 times higher plasma AUC). HA-Zein-CUR also led to enhanced delivery and accumulation of CUR in major organs/tissues, in particular CRC tumors and colon. These results together support that HA-Zein-CUR has promising potential as an oral agent for the control of CRC.